تصميم نظام تغذية كهروضوئي لإنارة عمود شارع من الطاقة الشمسية في مدينة اللاذقية - هلا مشقوق (Tishreen University, 2014)
ان الهدف من هذا البحث هو دراسة المتطلبات الفنية والاقتصادية لتصميم نظام إنارة مركب على برج كهربائي لإنارة شارع بالطاقة الكهربائية المولدة من خلايا شمسية، ثم نمذجة الدراسة الرياضية وفق برنامج بلغة الدلفي (Delphi)، ثم تطبيق الدراسة على شارعٍ كاملٍ. ثم اظهار نتائج البرنامج. وتطبيق الدراسة ممكن في أي شارعٍ. The objective of this research is a study the technical and economy prerequisite to design a complex light system on an electrical tower to light a street with electrical power that generated in solar cells. In addition, convert the mathematical study to program in Delphi language, then apply the study on a street completely, and finally appear the program results, it can also apply the study on any street.